Drimartol B, a sesquiterpene coumarin of the edible powder of Artemisia sphaerocephala seed, induced apoptosis in NSCLC cells via PI3K/AKT/FoxO3a pathway inhibition - Jiwen Li; Zhongyu Li; Mengru Cui; Mei Sun; Lei Men; Xiaojie Gong; Keke Li (Journal of Functional Foods)
In this study, Drimartol B, a sesquiterpene coumarin isolated from the edible powder of Artemisia sphaerocephala seeds, was investigated for its potential anti-NSCLC effects. Our findings showed that drimartol B inhibited the proliferation of both A549 and NCI-H1975 cells. Mechanistic studies revealed that Drimartol B induced cell cycle arrest, decreased mitochondrial membrane potential, reduced Bcl-2, and increased Bax, Caspase-9, and -3 levels, thereby promoting apoptosis. Additionally, network pharmacology identified the PI3K/AKT/FoxO3a pathway as a key target. Molecular docking demonstrated favorable binding affinities between drimartol B and these proteins. Moreover, the regulatory role of drimartol B in NSCLC cells via PI3K/AKT/FoxO3a pathway was confirmed by co-treatment with SC-79 or JY-2. Overall, our findings reveal that drimartol B exerts anticancer effects on NSCLC cells via modulation of the PI3K/AKT/FoxO3a pathway. The future perspective of drimartol B as a dietary component for NSCLC treatment suggests its possible utility in personalized nutrition approaches.